Interhelical H-Bonds Modulate the Activity of a Polytopic Transmembrane Kinase - Almada, Juan Cruz (Biomolecules, 2021)
DesK is a Histidine Kinase that allows Bacillus subtilis to maintain lipid homeostasis in response to changes in the environment. It is located in the membrane, and has five transmembrane helices and a cytoplasmic catalytic domain. The transmembrane region triggers the phosphorylation of the catalytic domain as soon as the membrane lipids rigidify. In this research, we study how transmembrane inter-helical interactions contribute to signal transmission; we designed a co-expression system that allows studying in vivo interactions between transmembrane helices. By Alanine-replacements, we identified a group of polar uncharged residues, whose side chains contain hydrogen-bond donors or acceptors, which are required for the interaction with other DesK transmembrane helices; a particular array of H-bond- residues plays a key role in signaling, transmitting information detected at the membrane level into the cell to finally trigger an adaptive response.